2011
DOI: 10.1016/j.lcats.2011.06.001
|View full text |Cite
|
Sign up to set email alerts
|

iPotential: Mobile electronic resource management on an iPad

Abstract: When out of the office for conferences or other obligations, those who manage e-resources must often take their work with them. With the advent of Apple's iPad, the authors made the decision to investigate the possibilities and potential offered by this new device for mobile management of electronic resources. To accomplish this, the authors used iPads to test the various systems and tools utilized every day to manage and maintain the library's electronic resources to find out what worked, and what didn't. Whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Hartnett and Price tested the potential of Apple's iPad as a mobile management tool. 30 They reviewed the tasks addressed in their work and investigated the availability of apps that would enable the iPad to do this work. While they found the iPad's size, the availability of both Wi-Fi and 3G service, and its intuitive interface LRTS 57 (2) advantageous, they concluded that problems with printing, file management, and working directly with a server limited the iPad's effectiveness.…”
Section: Additional Toolsmentioning
confidence: 99%
“…Hartnett and Price tested the potential of Apple's iPad as a mobile management tool. 30 They reviewed the tasks addressed in their work and investigated the availability of apps that would enable the iPad to do this work. While they found the iPad's size, the availability of both Wi-Fi and 3G service, and its intuitive interface LRTS 57 (2) advantageous, they concluded that problems with printing, file management, and working directly with a server limited the iPad's effectiveness.…”
Section: Additional Toolsmentioning
confidence: 99%